ANALISIS ISI PESAN HOAKS DI INSTAGRAM @TURNBACKHOAXID TENTANG VAKSIN COVID-19: (Periode Desember 2020 –Januari 2021) - Ayu Latifa; Ratnaningrum Zusyana Dewi; M.I. Asyarin Hayau Lailin (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2021)
Hoax is a form of fraudulent message that is made intentionally. Information that is factual is often mingled with hoaxes through social media. During the COVID-19 pandemic, many hoaxes emerged about the COVID-19 vaccine. Starting from the side effects, the dangers of the vaccine, the content of the vaccine, and much more. The purpose of this study was to find out the contents of hoax messages on Instagram @turnbackhoaxid about the covid-19 vaccine (December 2020-January 2021) Researchers get hoax messages from data that has been collected from the @turnbackhoaxid instagram account and then analyzed using content analysis with a qualitative descriptive approach. The results obtained that the hoax messages have the following characteristics: there is no news editor, the message is sensational, the content of the message conveyed contains discriminatory elements, there is no date of occurrence, the place of incident is not clear, the storyline is illogical. While the content of the word proactive could not be found. Then in the category of messages used that are expired, and contain elements of SARA, they can be found but in small quantities. In this case, it can be concluded that the vaccine hoax messages that appeared during the months of December 2020 to January 2021 did not contain proactive words containing an invitation to redistribute. In addition, the hoax messages made are generally in the form of personal opinions that focus on discussing the side effects of the covid-19 vaccine.